Ultrafine industrial aerosol as an occupational risk factor for sintering industry workers - L. P. Sharavara; N. M. Dmytrukha; I. M. Andrusyshyna (Сучасні медичні технології)
Aim. Assessment of the physicochemical characteristics of suspended particulate matter of the ultrafine range present in the air of the working area of the sintering factory of a metallurgical plant.